Rowley-Conwy, Peter (2007). From genesis to prehistory. The archaeological three age system and its contested reception in Denmark, Britain and Ireland. Oxford, Oxford University Press, 384 pp. ISBN: 978-019-922774-7 - Podgorny, Irina (2009)
Fil: Podgorny, Irina. Universidad de La Plata. Archivo Histórico; Argentina.